Dilemma of health rights of vulnerable citizens: a narrative review - Mumtaz, Nazia; Saqulain, Ghulam; Mumtaz, Nadir (Journal of the Pakistan Medical Association, 2022)
Vulnerable populations have traditionally faced non availability of health services. Enforcement of constitutional protections to vulnerable citizens is essential to secure them their health rights. Hence current narrative review in perspective of rights laws was conducted with the objective to review and highlight provisions of the constitution of different countries and World Health Organization (WHO) and the on ground situation prevailing in Pakistan. This study has immense significance, since this can invoke debate, inspire research and recognition of the enabling articles/ provisions for health care guaranteed in the Constitution. For this purpose data was searched for publications related to constitution and health of countries including Pakistan, United States, United Kingdom, China, Saudi Arabia and India using search engines, data bases and different websites. 170 reports, publications & articles were downloaded out of which 30 English, full text articles, publications and reports were utilized for the current research. Keywords: Vulnerable population,